The diagnostic value of cytology in the mammary intraductal lesions of patients with pathological nipple discharge - Yifei Zeng; Jifeng Li; Dongxiao Zhang; Na Fu; Yu Zhou; Yubo Guo; Min Liu; Hongkai Zhang; Jianchun Cui (Scientific Reports)
Abstract This study aimed to explore the diagnostic value of the two cytology techniques, including liquid-based cytology of mammary ductal lavage fluid and nipple discharge smear cytology, in the intraductal lesions in patients with pathological nipple discharge (PND). This retrospective analysis included 119 patients with PND who underwent surgical treatment. At the same time, they all underwent fiberoptic ductoscopy (FDS), nipple discharge smear cytology and liquid-based cytology of ductal lavage fluid before surgery. With postoperative pathological diagnosis as the gold standard, we compared the clinical diagnostic efficacy of the two cytology techniques applied independently and combined with FDS to evaluate their diagnostic value in intraductal lesions. Finally, the receiver operating characteristic (ROC) curves and the area under the curve (AUC) were used to evaluate the diagnostic value of each examination method. There were 22 breast malignant tumors, 75 intraductal papillomas and 22 non-tumorous lesions among the 119 PND patients. The cell types of liquid-based cytology of ductal lavage fluid was significantly more abundant than that of smear cytology, and the detection rate of tumor cells, atypia cells and atypical hyperplasia cells was significantly increased. The diagnostic accuracy and sensitivity of liquid-based cytology of ductal lavage fluid were significantly higher than that of smear cytology (P < 0.05). At the same time, the accuracy of liquid-based cytology was superior to that of smear cytology when combined with FDS (P < 0.05), and the diagnostic efficiency was excellent. FDS combined with liquid-based cytology of ductal lavage fluid was more effective than the other methods (AUC = 0.8182). When diagnosing the intraductal space-occupying lesions in PND patients, liquid-based cytology of ductal lavage fluid can obtain more abundant intraductal shed cells. This advantage can compensate for the limitation of FDS for diagnosing terminal ductal unit lesions and significantly improve the early diagnosis rate of intraductal lesions, especially intraductal malignant tumors.